Advances in analytical techniques for polychlorinated dibenzo-p-dioxins, polychlorinated dibenzofurans and dioxin-like PCBs - Reiner, Eric J. (Springer-Verlag, 2006)
Analytical techniques for the determination of polychorinated dibenzo-p-dioxins (PCDD), polychlorinated dibenzofurans (PCDF) and dioxin-like PCBs (DLPCB) are reviewed. The focus of the review is on recent advances in methodology and analytical procedures. The paper also reviews toxicology, the development of toxic equivalent factors (TEF) and the determination of toxic equivalent quantity (TEQ) values. Sources, occurrence and temporal trends of PCDD/PCDF are summarized to provide examples of levels and concentration ranges for the methods and techniques reviewed.